Metabolome and Microbiome Signatures in the Leaves of Wild Tea Plant Resources Resistant to Pestalotiopsis theae - Zhang, Yuqian; Zhang, Jie; Yan, Changyu; Fang, Meishan; Wang, Lijie; Huang, Yahui; Wang, Feiyan (Frontiers in Microbiology, 2022)
Tea (Camellia sinensis) is an important crop that is mainly used in the food industry. This study using the metabolome and microbiome investigates the resistance factors of wild tea plant resources against tea grey blight disease, which is caused by Pestalotiopsis theae (Sawada) Steyaert. According to the interaction analysis of tea leaves and pathogenic fungus, the resistance of wild tea plant resource ‘R1’ (Resistance 1) to tea grey blight disease was significantly higher than that of wild tea plant resource ‘S1’ (Susceptibility 1). The difference between ‘R1’ and ‘S1’ in the metabolome was obvious. There were 145 metabolites that significantly changed. The phenolic acids and flavonoids were the major increased categories in ‘R1’, and included 4-O-Glucosyl-sinapate and petunidin-3-o-(6''-o-p-coumaroyl) rutinoside. Six metabolic pathways were significantly enriched, including aminoacyl-tRNA biosynthesis, flavone and flavonol biosynthesis. In terms of bacteria, there was no significant difference between ‘S1’ and ‘R1’ in the principal component analysis (PCA). Pseudomonas was the major bacterial genus in ‘S1’ and ‘R1’. In addition, each of the two resources had its own predominant genus: Cellvibirio was a predominant bacterial genus in ‘S1’ and Candidatus_competibacter was a predominant bacterial genus in ‘R1’. In terms of fungi, the fungal diversity and abundance of the two tea plant resource samples could be distinguished clearly. The fungal component of ‘S1’ was more abundant than that of ‘R1’ at the genus level. Toxicocladosporium was the predominant fungal genus of ‘S1’, and Filobasidium was the predominant fungal genus of ‘R1’. The relative abundance of unclassified-norank-norank-Chloroplast and Penicillium were significantly different between ‘S1’ and ‘R1’. Penicillium was identified as a potential biomarker. They correlated with some metabolites enriched in ‘S1’ or ‘R1’, such as L-arginine and quercetin-3-o-(2''-o-rhamnosyl) rutinoside-7-o-glucoside. Overall, phenolic acids, flavonoids, and Penicillium could be functional metabolites or microorganisms that contributed to improving the resistance of wild tea plant resources to tea grey blight disease.